Kapasitas Kelembagaan Pemerintah Desa dalam Pengelolaan Badan Usaha Milik Desa di Kabupaten Sumedang - Idah Wahidah; Dian Herdiana (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
One of the goals of national development is the development that starts from the village, where one of the efforts is to build village-owned enterprises. Based on this understanding, this article is intended to analyze the management of Village-Owned Enterprises with a research question, namely, how is the institutional capacity of the village government in managing village-owned enterprises in Sumedang Regency. The research method used is a descriptive research method with a qualitative approach. The data come from primary research and secondary data from various relevant references. The study results revealed that the village government's institutional capacity in managing village-owned enterprises is already good; this is indicated by most village-owned enterprises in the Sumedang district, which are already developing and advanced. Good institutional capacity is shown by the individual attitude of administrators who can adequately manage village-owned enterprises and are supported by management that is in line with existing regulations.